2017
DOI: 10.3389/fnhum.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Transcranial Direct Current Stimulation Does Not Facilitate Dynamic Balance Task Learning in Healthy Old Adults

Abstract: Older adults frequently experience a decrease in balance control that leads to increased numbers of falls, injuries and hospitalization. Therefore, evaluating older adults’ ability to maintain balance and examining new approaches to counteract age-related decline in balance control is of great importance for fall prevention and healthy aging. Non-invasive brain stimulation techniques such as transcranial direct current stimulation (tDCS) have been shown to beneficially influence motor behavior and motor learni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 57 publications
0
52
1
3
Order By: Relevance
“…In contrast, Kaminski et al (28) showed that M1 tDCS did not affect balance learning in the elderly. Differences in the findings can be related to differences in the type of outcome, which was dynamic balance in the study by Kaminski et al (28) and static balance in the current study. In another study, Zhou et al (42) reported that a-tDCS could not change the duration of Timed Up and Go (TUG) test in older adults.…”
Section: Effect Of M1 Tdcs On Balancementioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, Kaminski et al (28) showed that M1 tDCS did not affect balance learning in the elderly. Differences in the findings can be related to differences in the type of outcome, which was dynamic balance in the study by Kaminski et al (28) and static balance in the current study. In another study, Zhou et al (42) reported that a-tDCS could not change the duration of Timed Up and Go (TUG) test in older adults.…”
Section: Effect Of M1 Tdcs On Balancementioning
confidence: 90%
“…a-tDCS of the cerebellum had no significant effects on balance (25)(26)(27). These controversial findings show that age is a factor, which may affect the outcomes of brain stimulation techniques (7,28,29).…”
Section: Effect Of Cerebellar Tdcs On Balancementioning
confidence: 93%
See 1 more Smart Citation
“…After completing the full-text review, one conference abstract and one study without providing study protocol were excluded. Ten studies examining the effects of tDCS on balance and mobility in older adults with relatively healthy status or with functional impairment (e.g., stroke, slow gait) (Kaski et al, 2013;Manor et al, 2015Manor et al, , 2018Saeys et al, 2015;Zhou et al, 2015Zhou et al, , 2018Ehsani et al, 2017;Kaminski et al, 2017;Nomura and Kirimoto, 2018;Yosephi et al, 2018) were accepted to be included in the systematic review and meta-analysis. Figure 2 illustrates the results of the Cochrane risk of bias tool.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the studies used sponge electrodes of the same size (i.e., 35cm 2 ) (Manor et al, 2015(Manor et al, , 2018Saeys et al, 2015;Zhou et al, 2015Zhou et al, , 2018Ehsani et al, 2017;Yosephi et al, 2018), while other three studies used electrodes of different sizes (Kaski et al, 2013;Kaminski et al, 2017;Nomura and Kirimoto, 2018). Kaminski et al (2017) for example, used smaller-size anodes and larger-size cathodes. The target current intensity of tDCS used in these studies was set as 1, 1.5 or 2 mA ( Table 2).…”
Section: Participant Characteristicsmentioning
confidence: 99%